The Influence of Pedagogical Competence and Learning Styles on Student Learning Outcomes in Economics Subjects In Public High School 2 Tapung Hilir - Anggy Pratama; Mahdum; Sumarno (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Learning outcomes are the achievements obtained by students after participating in educational activities in the form of the results of the assessment of the final semester exam in economics. There are several factors that can have an impact on student learning outcomes both from within and from outside, for example, the way of learning, the desire to learn, efforts to be independent and inspired, teacher teaching skills, facilities, social and cognitive environment, finance and community care. Thus, students must have good learning outcomes to realize behavioral changes to become a good person. The target of the exploration is to analyze the effect of teaching competence and learning style on student learning outcomes. The exploration involved Class XII social studies of SMA Negeri 2 Tapung Hilir. Random sampling method. The sample quantity was 92 students. Data were collected using a questionnaire. The data analysis method is multiple linear regression using SPSS. The results showed that teaching competence and teaching style have an impact on student learning outcomes. Teachers must have good teaching competencies such as understanding the condition and character of students, learning planning skills, skills in delivering learning using good methods, skills in assessing students' learning students' work and skills to develop students' potential. Students also need to understand and know their learning styles so that they can adapt their learning styles to the teaching methods offered by educators. This has an impact on children's achievement of better learning outcomes at school.